Revisiting the ontogenetic shift paradigm: The case of juvenile green turtles in the SW Atlantic - González Carman, Victoria (2012)
The green turtle (Chelonia mydas) is a subcosmopolitan species found in tropical and temperate latitudes. The best knowledge on its behavior described an abrupt and irreversible ontogenetic shift that takes place early in life in some areas such as the Greater Caribbean and Australia. Young turtles move from oceanic to neritic habitats, from pelagic to benthic feeding and from an omnivorous to an herbivorous diet. However, whether this pattern applies elsewhere in the range of the species is not known. In the temperate waters of the South West (SW) Atlantic, preliminary evidence suggests that these juveniles would not comply with the tenets of an abrupt and irreversible ontogenetic shift as in tropical waters. We satellite tracked 9 neritic juveniles moving along the coast of Argentina, and applied a switching state-space model combined with kernel density estimation to identify preferential putative foraging areas and migratory routes. Results indicate that immature green turtles are not strictly herbivores or neritic in the temperate SW Atlantic. In summer and fall, juveniles foraged most of the time in estuarine areas without submerged macrophytes. In winter and spring, the turtles migrated north to warm coastal areas where macroalgae and seagrass are available. Concomitant to pelagic feeding, some turtles reached deep water areas where macrophytes are unlikely to occur. Adaptation to local conditions explains behavior better for the SW Atlantic than the abrupt and irreversible ontogenic shift described for warmer waters.